The Influence of Green Marketing Strategy on Purchase Decisions Mediated by Purchase Interest (Case Study of Electric Cars at Prestige MotorCars Indonesia) - Andryan, Dwi; Djatmika W.W, Ery Try; Suharsono, Naswan (University of Merdeka Malang, 2024)
The rapid advancement of environmentally sustainable technologies is evident in the global transition towards electric energy, particularly in the transportation sector, as numerous nations endeavor to reduce dependence on fossil fuels. This study investigates the multifaceted relationships between green marketing, consumer purchasing decisions, and purchasing intention in the context of electric vehicles. Specifically, it examines the direct influence of green marketing on consumer purchasing decisions and purchasing intention. Subsequently, the impact of purchasing intention on purchasing decisions, and the mediating role of purchasing intention in the relationship between green marketing and purchasing decisions. The research employs quantitative approach, utilizing a sample of 180 upper-middle-class electric car consumers from Prestige MotorCars Indonesia. Data analysis was conducted using SPSS 25. The findings showed statistically significant positive effects across all examined relationships: green marketing directly influences purchasing decisions, green marketing positively affects purchasing intention, purchasing intention significantly impacts purchasing decisions, and purchasing intention mediates the relationship between green marketing and purchasing decisions among electric car customers at Prestige MotorCars Indonesia. These results contribute to the understanding of consumer behavior in the evolving electric vehicle market and highlight the importance of green marketing strategies in influencing consumer decision-making processes.